Human capital and gender inequality in middle-income countries : schooling, learning and socioemotional skills in the labour market - King, Elizabeth M.; Gunewardena, Dileni (Abingdon, Oxon ; New York, NY : Routledge, Taylor & Francis Group, 2023)
The role of cognitive and socioemotional skills alongside education in determining people's success in the labour market has been the topic of a growing body of research -- but previous studies have mostly missed middle-income countries and the developing world because measures of those skills and data on employment and earnings on large enough samples of adults have typically not been available. Using comparable survey data on these schooling, skills and labour market outcomes from 13 developing and emerging economies worldwide, this book revisits human capital and gender inequality models. It presents new estimates of the returns to different levels of schooling as well as cognitive and socioemotional skills for women and men. It examines whether those returns are due to levels of human capital or to structural bias in labour markets, and how these two factors work across the earnings spectrum. The book examines the existence of 'glass ceilings' and 'sticky floors' for women using this expanded measure of human capital. Further, by analyzing a group of countries of wide-ranging levels of economic development and socio-political contexts, the book reveals patterns and insights into how context mediates the relationship between skills and gender gaps in labour market outcomes. This book will be of interest to scholars of human capital and gender inequality in the labour market and development economics, as well as gender and development policy makers.--
Human capital, gender and labour markets -- A human capital model of gender inequality in the workplace -- The premium to education and cognitive skills -- The premium to socioemotional skills in the labour market -- Education and skills, glass ceilings and sticky floors -- Human capital : Challenges and roads to gender equality.
Keywords: Human capital -- Developing countries; Labor supply -- Effect of education on -- Developing countries; Sex discrimination in employment -- Developing countries; Women -- Employment -- Developing countries; BUSINESS & ECONOMICS / Economic Conditions; BUSINESS & ECONOMICS / Education; BUSINESS & ECONOMICS / Labor